Research Progress on Internal Shear Connection of Double Steel Plate-concrete Composite Shear Wall. Issue 3 (March 2020) - Zhang, Zhuangnan; Shi, Rui; Cheng, Daye
Abstract: A comprehensive analysis of three types internal shear connection of double steel plate-concrete composite shear walls is carried out. There are internally welded shear connectors, tension restraints shear connectors, and cavity-type. The analysis shows that these three types of shear connection forms have significant effects on the improvement of the seismic performance of shear walls, and can give full use of the properties of steel and concrete. Compared with the traditional shear wall, the steel plate concrete shear wall has been greatly improved and has a high level of industrialization. Aiming at these three types of shear connection forms, their deficiencies and future development directions were clarified.